2009
DOI: 10.1021/jp9047709
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive DFT and MP2 Level Investigations of Reaction of 2,3-Dihydro-1,5-benzodiazepine-2-thiones with Hydrazine

Abstract: Density functional theory approach was used for the 4-phenyl-2,3-dihydro-1,5-benzodiazepine-2-thione compound to determine the mechanism of hydrazinolysis of 4-substituted 2,3-dihydro-1,5-benzodiazepine-2-thiones. Single-point calculations at the MP2/6-311+G(d,p)//B3LYP/6-311+G(d,p) level were performed for the more accurate energy prediction. The solvent effect was taken into account by carrying out single-point calculations using the PCM methodology. The obtained results show that in the investigating mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The synthesis and reactions of benzodiazepin-2-ones and thiones have been studied in detail by our group (Gaponov et al, 2016;Okovytyy et al, 2009). The mechanism of ethanolassisted hydrazinolysis of 1,3-dihydro-2H-benzo [b][1,4]diazepine-2-thiones ( Fig.…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis and reactions of benzodiazepin-2-ones and thiones have been studied in detail by our group (Gaponov et al, 2016;Okovytyy et al, 2009). The mechanism of ethanolassisted hydrazinolysis of 1,3-dihydro-2H-benzo [b][1,4]diazepine-2-thiones ( Fig.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The mechanism of ethanolassisted hydrazinolysis of 1,3-dihydro-2H-benzo [b][1,4]diazepine-2-thiones ( Fig. 1) has been modelled by quantumchemical calculations (Okovytyy et al, 2009). However, instead of obtaining the previously suggested products (IIIa) and (IIIb), compounds N 1 -(5-phenyl-1H-pyrazol-3-yl)benzene-1,2-diamine (Ia) and its 5-chloro-derivative (Ib) were prepared from 4-phenyl-1,3-dihydro-2H-benzo [b][1,4]diazepine-2-thiones (IIa) and (IIb) and hydrazine hydrate ( Fig.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Full gas-phase geometry optimizations were performed using the density functional theory with the Beck's three-parameter nonlocal exchange functional and the gradient-corrected functional of Lee et al (B3LYP), [72][73][74] due to its successful application in a number of hydrazinolysis [75,76] and analogous substituted hydrazine systems, [9,11,12] obtaining reasonable molecular structures, vibrational frequencies, and bond energies. Basis set of double-f split valence plus polarization and diffusion quality (6-31þG(d,p)) [77] was employed in all optimization calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Despite the abundance of data based on experimental results, only a few studies have dealt with the overall mechanism of nucleophile addition reactions. Okovytyy and co-workers described the hyrazinolysis mechanism of 2,3-dihidro-1,5-benzodiazipine-2-thiones and the 2,3-dihidro-1,5-benzodiazipin-2-ones . They have examined in detail the possible mechanisms of the initial step of the reactions and concluded that the benzodiazipine systems were attacked by a hydrazine molecule toward the azomethine bond.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundance of data based on experimental results, only a few studies have dealt with the overall mechanism of nucleophile addition reactions. Okovytyy and co-workers described the hyrazinolysis mechanism of 2,3-dihidro-1,5-benzodiazipine-2-thiones and the 2,3-dihidro-1,5-benzodiazipin-2-ones .…”
Section: Introductionmentioning
confidence: 99%